Modulation of the substorm current wedge by bursty bulk flows: 8 September 2002—Revisited. Issue 5 (26th May 2016) - Palin, L.; Opgenoorth, H. J.; Ågren, K.; Zivkovic, T.; Sergeev, V. A.; Kubyshkina, M. V.; Nikolaev, A.; Kauristie, K.; van de Kamp, M.; Amm, O.; Milan, S. E.; Imber, S. M.; et al.
Abstract: The ultimate formation mechanism of the substorm current wedge (SCW) remains to date unclear. In this study, we investigate its relationship to plasma flows at substorm onset and throughout the following expansion phase. We revisit the case of 8 September 2002, which has been defined as "one of the best textbook examples of a substorm" because of its excellent coverage by both spacecraft in the magnetotail and ground‐based observatories. We found that a dense sequence of arrival of nightside flux transfer events (NFTEs; which can be understood as the lobe magnetic signature due to a bursty bulk flow travelling earthward in the central plasma sheet) in the near‐Earth tail leads to a modulation (and further step‐like builtup) of the SCW intensity during the substorm expansion phase. In addition, we found that small SCWs are created also during the growth phase of the event in association with another less intense sequence of NFTEs. The differences between the sequence of NFTEs in the growth and expansion phase are discussed. We conclude that the envelope of the magnetic disturbances which we typically refer to as an intense magnetic substorm is the result of a group or sequence of more intense and more frequent NFTEs. Key Points: A localized substorm onset current wedge is modulated stepwise Buildup of the SCW is due to a dense sequence of arrival of BBFs in the near‐Earth tail An intense substorm is the result of a group or sequence of more intense and more frequent BBFs